2018
DOI: 10.1016/j.neures.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative differences in offline improvement of procedural memory by daytime napping and overnight sleep: An fMRI study

Abstract: Daytime napping offers various benefits for healthy adults, including enhancement of motor skill learning. It remains controversial whether napping can provide the same enhancement as overnight sleep, and if so, whether the same neural underpinning is recruited. To investigate this issue, we conducted functional MRI during motor skill learning, before and after a short day-nap, in 13 participants, and compared them with a larger group (n=47) who were tested following regular overnight sleep. Training in a sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Results disclosed rsFC changes between post-(RS 2) and pre-(RS 1) learning in the theta band (p = 0.004) and replicated induction effects in the boost window (RS 3 vs. RS 2) in the delta, alpha, beta and gamma bands (all p-values ≤ 0.03), and in the next day window (RS 7 vs. RS 6) within the alpha and gamma frequency bands (all p-values ≤ 0.05) [Supplementary Figs. [5][6][7][8][9][10][11]. No induction effects were evidenced in the silent window (RS 5 vs. RS 4), all p-values ≥ 0.22.…”
Section: Resting-state Functional Connectivity Analysesmentioning
confidence: 80%
“…Results disclosed rsFC changes between post-(RS 2) and pre-(RS 1) learning in the theta band (p = 0.004) and replicated induction effects in the boost window (RS 3 vs. RS 2) in the delta, alpha, beta and gamma bands (all p-values ≤ 0.03), and in the next day window (RS 7 vs. RS 6) within the alpha and gamma frequency bands (all p-values ≤ 0.05) [Supplementary Figs. [5][6][7][8][9][10][11]. No induction effects were evidenced in the silent window (RS 5 vs. RS 4), all p-values ≥ 0.22.…”
Section: Resting-state Functional Connectivity Analysesmentioning
confidence: 80%
“…The vast majority of sleep and memory research has been conducted in either whole night sleep or nap sleep designs and several studies directly investigated whether the chosen sleep protocol directly affects sleep-memory associations (Cousins et al, 2021; Lo et al, 2014; Mednick et al, 2003; Pöhlchen et al, 2021; Sugawara et al, 2018), especially with regards to the role of sleep spindles in memory consolidation (Cousins et al, 2021; van Schalkwijk et al, 2019). A recent study on procedural memory observed naps and whole nights of sleep may both yield similar memory benefits, suggesting that daytime naps protect memories from deterioration, whereas whole night sleep improves performance, especially in procedural memory (van Schalkwijk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Napping appears beneficial for all types of memory, either procedural [ 56 ], declarative [ 57 ] or short-term memory [ 19 ]. Daytime napping offers various other benefits such as relaxation, reduced fatigue [ 58 ] and improve mood [ 55 ]. Napping can boost creativity [ 59 , 60 ] and productivity [ 61 ], improve physical performance [ 62 ] and help people to cope with fatigue related to shiftwork [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%